Cross-Kerr nonlinearity in the surface plasmon polariton waves generated at the interface of graphene and gain medium. (18th July 2018) - Rahman, Habibur; Bibi, Haseena; Abdul Jabar, M. S.; Ahmad, Iftikhar
Abstract: Surface plasmon polariton (SPP) waves generated at the interface of graphene and a gain-assisted medium due to the effective Kerr nonlinear variation of the dielectric function are controlled and modified. The gain doublet in the SPP waves is measured at the interface with collective cross-Kerr nonlinear probe signals which generates Kerr nonlinearity in the SPPs. The alternate normal and anomalous dispersion of SPPs is controlled under Kerr nonlinearity and strength of the control fields, leading to slow and fast SPPs propagation. Further, the propagation length of SPPs is controlled under Kerr nonlinearity and strength of the control fields. The controlled SPPs show significant importance for optical tweezers, radiations guiding, nano-photonics, plasmonster technology, photovoltaic devices, data storage, solar cells and biosensor technology.